2019
DOI: 10.1371/journal.pone.0217635
|View full text |Cite
|
Sign up to set email alerts
|

Using sibling data to explore the impact of neighbourhood histories and childhood family context on income from work

Abstract: Previous research has reported evidence of intergenerational transmissions of neighbourhood status and social and economic outcomes later in life. Research also shows neighbourhood effects on adult incomes of both childhood and adult neighbourhood experiences. However, these estimates of neighbourhood effects may be biased because confounding factors originating from the childhood family context. It is likely that part of the neighbourhood effects observed for adults, are actually lingering effects of the fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Using data from the Netherlands, they show that the observed impact of the neighbourhood on an s after adding the neighbourhood selection controls, but remains significant. In another study, Hedman, Manley and van Ham (2019) used sibling data to explore the impact of neighbourhood histories and childhood family context on income from work. They concluded that there is a neighbourhood effect on income from adult neighbourhood experiences, but that the childhood neighbourhood effect is actually a childhood family context effect.…”
Section: Empirical Studies Of the Role Of Spatial Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Using data from the Netherlands, they show that the observed impact of the neighbourhood on an s after adding the neighbourhood selection controls, but remains significant. In another study, Hedman, Manley and van Ham (2019) used sibling data to explore the impact of neighbourhood histories and childhood family context on income from work. They concluded that there is a neighbourhood effect on income from adult neighbourhood experiences, but that the childhood neighbourhood effect is actually a childhood family context effect.…”
Section: Empirical Studies Of the Role Of Spatial Contextmentioning
confidence: 99%
“…They found that there is a longlasting effect of the family context on income later in life, and that this effect is strong regardless of the individual neighbourhood pathway later in life. Hedman et al (2019) provide a useful overview of some of the more recent literature on spatial context effects. Using data from the US, Chetty, Hendren and Katz (2016) demonstrate that moving from a high-to a lower-poverty area before the age of 13 is associated with increased college attendance, and higher earnings and lower risks of single parenthood later in life.…”
Section: Empirical Studies Of the Role Of Spatial Contextmentioning
confidence: 99%
“…The literature on neighbourhood effects increasingly stresses the importance of timed effects, longer time frames and intergenerational transmission. Empirical analyses demonstrate that effects linger and that childhood neighbourhood exposure affects life chances of individuals well into adulthood (Chetty, Hendren, & Katz, 2016;Galster & Santiago, 2017;Hedman, Manley, & van Ham, 2019;Hedman, Manley, van Ham, & Östh, 2015;Sampson, Sharkey, & Raudenbush, 2008;Sharkey, 2008). Sharkey and Elwert (2011) take the analysis one step further and show that cognitive abilities of children are substantially reduced (by more than half a standard deviation) if their families have been exposed to poverty for two consecutive generations.…”
Section: Neighbourhood Deprivation and Affluence As Multigenerational Phenomenamentioning
confidence: 99%
“…Ultimately, neighbourhood effects research should be reconciled with more individual- and family-oriented perspectives on human development, by recognising the key lower-level context – the family, and its mediating position between an individual and the neighbourhood (Lee, 2001; Hedman et al, 2019), as well as the interaction of other factors, such as genes, with the environment (see e.g. Boardman et al, 2013).…”
Section: Structuring the Uncertainty Of Sociospatial Contextmentioning
confidence: 99%